2018
DOI: 10.1111/1471-0528.15412
|View full text |Cite
|
Sign up to set email alerts
|

FAS A‐670G and Fas ligand IVS2nt A 124G polymorphisms are significantly increased in women with pre‐eclampsia and may contribute to HELLP syndrome: a case‐controlled study

Abstract: Polymorphisms in the Fas and FasL genes are associated with increased risk of pre-eclampsia and HELLP syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
1
10
0
1
Order By: Relevance
“…Consistent with these findings, we and others have also shown that the expression of FAS and FASL in serum and in maternal lymphocytes also occurs in preeclampsia (Miko et al, 2009;Raguema et al, 2018). We also described the polymorphisms of FAS-670A/G and FASL IVS2nt124A/G genes in the lymphocytes of pregnant women with preeclampsia.…”
Section: Apoptosis In Preeclampsiasupporting
confidence: 89%
“…Consistent with these findings, we and others have also shown that the expression of FAS and FASL in serum and in maternal lymphocytes also occurs in preeclampsia (Miko et al, 2009;Raguema et al, 2018). We also described the polymorphisms of FAS-670A/G and FASL IVS2nt124A/G genes in the lymphocytes of pregnant women with preeclampsia.…”
Section: Apoptosis In Preeclampsiasupporting
confidence: 89%
“…It has been reported that extravillous trophoblast cells (EVTs) express FAS-L [17], thus implying that FAS-L expression in both maternal and fetal cells represents an additional mechanism related to the immunotolerance phenomenon in pregnancy [18]. Genetic variants in the regulatory region of FAS and FAS-L genes have been shown to impact gene expression patterns and the susceptibility of many immunerelated disorders and pregnancy disorders, including RPL [19][20][21][22][23][24][25][26][27]. FAS-670A/G and FAS-1377G/A are single nucleotide polymorphisms (SNPs) that are located in the promoter region of FAS.…”
Section: Introductionmentioning
confidence: 99%
“…Nine citations were excluded due to the following reasons: two citations did not provide detailed genotyping data; four studied other diseases, and three was not case–control study. Eventually, we identified seven eligible citations [14–20] (834 cases and 1072 controls) containing nine studies. Selection for qualified studies was shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several studies [14–20] reported the association between single-nucleotide polymorphisms (SNPs) in Fas, FasL genes and the risk of preeclampsia. However, the results were inconsistent and conflicting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation